Bank Ownership, Market Structure and Risk - De Nicolo, Gianni (IMF Working Papers; Working Paper ;, 2007)
This paper presents a model of a banking industry with heterogeneous banks that delivers predictions on the relationship between banks' risk of failure, market structure, bank ownership, and banks' screening and bankruptcy costs. These predictions are explored empirically using a panel of individual banks data and ownership information including more than 10,000 bank-year observations for 133 non-industrialized countries during the 1993-2004 period. Four main results obtain. First, the positive and significant relationship between bank concentration and bank risk of failure found in Boyd, De Nicolo and Al Jalal (2006) is stronger when bank ownership is taken into account, and it is strongest when state-owned banks have sizeable market shares. Second, conditional on country and firm specific characteristics, the risk profiles of foreign (state-owned) banks are significantly higher than (not significantly different from) those of private domestic banks. Third, private domestic banks do take on more risk as a result of larger market shares of both state-owned and foreign banks. Fourth, the model rationalizes this evidence if both state-owned and foreign banks have either larger screening and/or lower bankruptcy costs than private domestic banks, banks' differences in market shares, screening or bankruptcy costs are not too large, and loan markets are sufficiently segmented across banks of different ownership.